Effects of Supplemental Irrigation on Yield and Yield Components of Spring Safflower Genotypes - Ahmad Tobeh, Hossein Mostafaii, Mashaalah Jabbari, Ali Ebadi (Recent Research in Science and Technology, 2009)
In order to evaluate the effect of supplemental irrigation on yield and yield components of spring safflower genotypes, an experiment was conducted with four irrigation levels (none irrigation, irrigation at heading, flowering and heading + flowering stages) and three safflower genotypes (Gilla, Isfahan land race and PI-537636) in a split plot experiment based on complete block design with three replications in Agricultural Research Station of Ardabil in 2008. In this study effects of irrigation levels and genotypes on plant height, number of seed per head, 1000-grain weight, kernel to seed coat ratio, biological yield, harvest index, oil and seed yield was significant. Irrigation at heading and flowering stages were most efficient. Also there was significantly interaction between irrigation and genotypes in kernel / seed coat ratio and seed yield. Isfahan land race genotype with irrigation at heading and flowering stages had the best treatment combination.